Forensic and pharmaceutical research of organization of availability of the medicines for patients with malignancies in the United States - Shapovalov, V (Jr.); Zbrozhek, S; Shapovalova, V; Shapovalov, V; Kulykova, O (Annals of Mechnikov’s Institute, 2020)
Introduction. The incidence of cancer in recent years has increased significantly. It is therefore particularly important today is the issue of provision for patients with malignancies with drugs. It is important to research the level of organization of availability of the anesthetic therapy to ensure the availability of pharmacotherapy for cancer patients worldwide. Material and methods. For the purpose of the study analyzed legislation, regulations of some states in the US that provide availability of narcotic analgesic drugs for patients with malignant neoplasms. The paper used the following methods: comparative, documentary, legal, medical, pharmaceutical and graphical analysis. Results and discussion. Noted the increase in expenditure on pharmaceutical provision for patients with malignancies on an outpatient basis in the US. During the study of the legislative and regulatory acts of the USA found that payments for treatment possible by insurance companies as part of the agreement, which in turn depend on the patient’s age, number of family members, their total income and so on. Coupons can be used to pay for the cost of medicines, but not all pharmacies accept coupons. There are charities with funds which are partially covered for the cost of chemotherapy and adjuvant therapy (analgesics, antiemetic, antipsychotics, drugs). Found, that in New York doctor may prescribe analgesic medication to the patient without limitation in the frequency and dose. It is not therapeutic use of analgesics, their improper accounting, drug addiction patient has contraindications to the prescription of narcotic analgesic drugs with malignant neoplasms. Reviewed examples from forensic and pharmaceutical practice, pharmaceutical violation of the US laws that regulate the accessibility of patients with malignancies to narcotic analgesic drugs. So, there have been cases of fake prescriptions for narcotic drugs, selling drugs, the shelf life has expired. Police of New Jersey the fact of abduction of injectable morphine and its falsification of employee hospital. Conclusion. Conducted a study of the availability of narcotic analgesic drugs for patients with malignancies in the US from a position of forensic pharmacy. Made an analysis of mortality from malignancies worldwide. Studied pharmaceutical legislation of Nevada, Texas, Georgia, New York in the pharmaceutical industry of providing patients with malignancies with narcotic analgesic drugs.